PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS DI MAKASSAR. - Andi Farid; Siti Haerani; Nurdjanah Hamid; Andi Reni (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
In achievement organizational goals, the teachers as human resources play a very important role to other resources in the Organization. Improving teacher performance, occupying important and strategic positions. The Science and technology as capital by human resources will be more effective if handled by capable human resources and have high performance. Therefore, this research aimed to analyze the influence of Organizational Culture, Organizational Commitment, and Job Satisfaction on the Performance of the teachers of state high School in Makassar. This research used quantitative method. The research sample was 89 teachers in the school. The techniques used to collect data were the questionnaires observation, and the various data with were related to the research. The analysis method used in this research was the SEM PLS 3.0 analysis with SPSS 22. The results indicated that organizational culture, organizational commitment, and job satisfaction had a positive and significant effect on teacher’s performance.